Associations between the household environment and stunted child growth in rural India: a cross-sectional analysis - Lee, C; Lakhanpaul, M; Maza Stern, B; Sarkar, K; Parikh, P (UCL Press, 2021)
Stunting is a major unresolved and growing health issue for India. Yet there remains scant evidence for the development and application of integrated, multifactorial child health interventions across Indias most rural communities. We examine the associations between household environmental characteristics and stunting in children under 5 years across rural Rajasthan, India. We used DHS-3 India data from 1194 children living across 109,041 interviewed households. Multiple logistic regression analyses independently examined the association between (1) main source of drinking water, (2) main type of sanitation facilities, (3) main cooking fuel type, and (4) agricultural land ownership and stunting adjusting for child age. After adjusting for child age, household access to (1) improved drinking water source was associated with a 23% reduced odds (OR=077, 95% CI 05 to 100), (2) improved sanitation facility was associated with 41% reduced odds (OR=051, 95% CI 03 to 082), and (3) agricultural land ownership was associated with a 30% reduced odds of childhood stunting (OR 070, 95% CI 051 to 094). Cooking fuel source was not associated with stunting. Although further research is needed, intervention programmes should consider shifting from nutrition-specific to nutrition-sensitive solutions to address Indias childhood malnutrition crisis. Results and implications are discussed.